HUBUNGAN ANTARA SENSE OF HUMOR DENGAN KECEMASAN YANG DIRASAKAN MAHASISWA AKTIF UNIKA ATMA JAYA - Joy Gabriella Tatu; Clara Ajisuksmo; Desy Chrisnatalia (MANASA, 2023)
University students often face challenges both in the academic and non-academic fields. The pressures felt by these students can cause anxiety in students. Anxiety that exists in students can cause negative impacts that can harm students. Based on the previous research, it has been found that a sense of humor has a relationship with anxiety and can help overcome this anxiety. Therefore, this study aims to determine the relationship between a sense of humor and anxiety feltby active students at Atma Jaya Catholic University of Indonesia (Unika). The study used a quantitative approach with a correlation research design. The subjects of this study were 396 active students at Unika Atma Jaya. The research instruments used were the Multidimensional Sense of Humor Scale (MSHS) to measure Sense of Humor and the Hamilton Anxity Rating Scale (HAM-A) to measure anxiety. The results of this study were that there was no significant relationship between Sense of Humor and the anxiety felt by active students at Unika Atma Jaya.